Corporate governance, the GFC and independent directors. Issue 4 (5th May 2015) - Williams, Belinda Rachael; Bingham, Simone; Shimeld, Sonia
Abstract : Purpose: – The purpose of this study is to understand how board composition and independent non-executive director (INED) disclosures have changed in light of the global financial crisis (GFC) from an accountability perspective. Design/methodology/approach: – Content analysis techniques were undertaken on a random sample of 75 publicly listed companies across two time periods, 2005 and 2010. Findings: – The findings highlighted increased INED board membership and increased skill and experience disclosure across all board positions, with the most significant increase being the INED position. The results support the notion that firms are attempting to restore their accountability relationships post-GFC through more transparent mechanisms of governance. However, concerns are also raised in the way individual companies are meeting the ASX Corporate Governance independence requirements. Research limitations/implications: – The results raise questions as to whether firms have implemented these changes to ensure effective governance and accountability responsibilities, or simply to give the appearance of good governance. Originality/value: – Little attention has been given in the literature to the characteristics of INEDs and whether board changes have been made in the wake of corporate and financial crises. The findings from this study contribute to an understanding of board composition and disclosures pre- and post-GFC.